THE FERN-GENUS PLEOCNEMIA PRESL - HOLTTUM, R. E. (Research Center for Biology, 1951)
Â Â 1. The genus Pleocnemia Presl is redefined and differentiated from Tectaria Cav. and Arcypteris Underw., the latter genus being very closely related to Pleocnemia. 2. The configuration of the perispore proved to be of importance for the characterisation of the .species. In this regard three types are distinguished, perispore 1 forming crisped anastomosing wings, perispore consisting of many slender spines, and, an intermediate type, perispore forming many small separate wings.3. Tentatively 15 species are recognized. Of these, Pleocnemia winitii Holttum,P. acuminata Holttum, P. pleiotricha Holttum, P. presliana Holttum, P. dimidiolobata Holttum, P. tripinnata Holttum, and P. seranensis Holttum are described as new, aa well as one variety, P. conjugata var. elatior Holttum. 4.The following new combinations are made:P.hemiteliiformis (Racib.)Holttum (basinym:Pleocnemia leuzeana var. hemiteliaeformis Racib.),P.olivacea (Copel.)Holttum (basinym: Tectaria olivacea Copel.),P. kingii (Copel.) Holttum (basinym: Tectaria kingii Copel.), and P. chrysotricha (Bak.) Holttum (basinym: Nephrodium chrysotrichum Bak.). 5. Reductions to synonymy are: Pleocnemia javanica Presl to P. conjugata (Bl.) Presl, and Dictyopteris compitalis v. A. v. R. to P. hemiteliiformis (Racib.) Holtt